Answer:
![y=-\,(x+1)^2+3](https://img.qammunity.org/2021/formulas/mathematics/college/6gut8ow5v3xqeyrwe1o6gqjmldrxpgnhbx.png)
Explanation:
Notice that the vertex of the parabola is at (-1, 3), so we can start the expression of the quadratic in vertex form as:
![y=a\,(x--1)^2+3\\y = a\,(x+1)^2+3](https://img.qammunity.org/2021/formulas/mathematics/college/3v0ukh27q0ar7e9vg29qttywmy0ltqj8tf.png)
we can now find the coefficient "a" by using another point the parabola goes through, like for example (0,2):
![y = a\,(x+1)^2+3\\2=a\,(0+1)^2+3\\2=a+3\\a=2-3\\a=-1](https://img.qammunity.org/2021/formulas/mathematics/college/jkk97hy6siaqrp4oro58l8htul25e7nktc.png)
So the final expression for the parabola in vertex form is:
![y=-\,(x+1)^2+3](https://img.qammunity.org/2021/formulas/mathematics/college/6gut8ow5v3xqeyrwe1o6gqjmldrxpgnhbx.png)